Visual disturbance with systemic symptoms: old lessons revisited. (25th October 2016) - Hume, Megan E; Fernandes, Peter M; MacLean, Kirsty; McRorie, Euan; Davenport, Richard
Abstract : We describe a retired physician who presented with visual disturbance and systemic symptoms. The presence of general malaise, headache and scalp tenderness, with raised inflammatory markers, suggested that giant cell arteritis (GCA) was the likely diagnosis. Rapid response to initial steroid therapy and histological evidence of inflammation in the temporal artery supported this diagnosis. The character of these visual symptoms was, however, atypical for GCA. The patient, who had heart valve disease, subsequently deteriorated and developed further symptoms warranting investigation of bacterial endocarditis. Retinal emboli are a recognised complication of endocarditis, which could account for these visual symptoms. Moreover, interpretation of the temporal artery biopsy is limited in the context of existing steroid therapy. Our patient was consequently diagnosed with bacterial endocarditis. This case reminds us to consider the wider differential diagnoses for headache, visual disturbance and systemic symptoms, where echocardiogram and blood cultures may be crucial to reach the diagnosis.